Trace metal modified perovskite oxide, catalyst and method

By introducing a vulcanized layer and a trace metal modification layer on the substrate of the perovskite oxide catalyst, the problems of insufficient conductivity and low active sites in electrochemical applications are solved, and a significant improvement in catalytic performance and economic and stability are achieved.

CN119506963APending Publication Date: 2025-02-25HUANENG YIMIN COAL POWER CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411729004.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing perovskite oxide catalysts face the problems of insufficient conductivity and low active sites in electrochemical applications, and the catalysts are insufficient economic and stability, making it difficult to meet the needs of commercial applications.

Method used

By introducing a vulcanized layer and a trace metal modified layer on the LaMO3 perovskite oxide substrate, a trace metal modified perovskite oxide catalyst was prepared by combining sol-gel method and high-temperature calcination.

Benefits of technology

It significantly improves the catalytic performance and structural stability of perovskite oxides, improves their activity and selectivity in electrochemical reactions, extends the service life of the catalyst, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506963A_ABST
    Figure CN119506963A_ABST
Patent Text Reader

Abstract

The invention provides a trace metal modified perovskite oxide, a catalyst and a method, the trace metal modified perovskite oxide comprises a LaMO3 type perovskite oxide substrate, a vulcanization layer and a trace metal modification layer, the vulcanization layer and the trace metal modification layer are sequentially arranged on the surface of the LaMO3 type perovskite oxide substrate, and M is non-noble metal. On the basis of considering economy and performance, the catalytic performance of the perovskite oxide is improved, so that the application of the perovskite oxide in electrochemical reaction is promoted, and commercial application requirements are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrochemical technology, and in particular to a trace metal-modified perovskite oxide, a catalyst and a method. Background Art

[0002] At present, electrochemical technology is developing rapidly, and technologies such as water electrolysis, electrochemical CO2 reduction, and electrochemical ammonia synthesis have received widespread attention. With the rapid development of renewable energy, electrochemical technology has ushered in opportunities for commercial and large-scale applications. However, the above technologies still face the challenge of insufficient economic efficiency of core materials and components. For example, technologies such as water electrolysis still require the use of relatively expensive catalysts, which increases their application costs, and catalysts often face the problem of deactivation, and long-term stability cannot be guaranteed. Therefore, it is urgent to develop efficient and stable catalysts to lay the foundation for the application of electrochemical technology.

[0003] Perovskite oxides have a unique high-tolerance ABO3-type crystal structure, flexible elemental composition, and adjustable electronic structure. They show outstanding stability in traditional thermal catalytic reactions and key electrochemical reactions such as hydrogen evolution reaction (HER), oxygen evolution reaction (OER), and oxygen reduction reaction (ORR). However, perovskite catalysts often face problems of insufficient conductivity and relatively low active sites in electrochemical applications. Currently, researchers are exploring various strategies such as element doping, nanostructure engineering, and defect regulation, combined with advanced characterization methods such as X-ray absorption spectroscopy (XAS) and Raman spectroscopy to analyze and optimize the electrocatalytic performance of perovskite oxides. For example, Zhou et al. used a sol-gel and calcination method to prepare 80nm nano-LaCoO3 (LCO) particles. Nat Commun 7, 11510 (2016)], compared with bulk LCO particles, the active area and active sites are effectively increased, which promotes the improvement of OER performance; Patent CN 110280237A discloses a microwave-prepared perovskite oxide for oxygen reduction catalysis, which reduces La 0.5 Sr 0.5 The synthesis temperature of MnO3 perovskite oxide significantly improved the ORR performance; Yu Shuhong and Gao Minrui's research team reported a template-assisted strategy to synthesize 13 perovskite oxides with high surface area and tubular nanostructures, which effectively improved the OER performance. However, in terms of improving the catalytic activity of perovskite oxides, it is still necessary to develop a simple and highly reproducible synthesis method to achieve large-scale application. Summary of the invention

[0004] In order to solve the problems existing in the prior art, the present invention proposes a trace metal-modified perovskite oxide, catalyst and method, aiming to improve the catalytic performance of perovskite oxide on the basis of taking into account both economy and performance, so as to promote its application in electrochemical reactions and meet the needs of commercial applications.

[0005] To achieve the above-mentioned purpose, the present invention provides the following technical solution: a trace metal modified perovskite oxide, comprising a LaMO3 type perovskite oxide substrate, a sulfide layer and a trace metal modification layer, the sulfide layer and the trace metal modification layer are sequentially arranged on the surface of the LaMO3 type perovskite oxide substrate, wherein M is a non-precious metal.

[0006] Furthermore, in the LaMO3-type perovskite oxide, the molar ratio of La to M is 1:1.

[0007] Furthermore, in the LaMO3-type perovskite oxide substrate, M is one or two of nickel, iron, cobalt, and manganese; and the metal used in the trace metal modification layer is silver, gold, copper, or platinum.

[0008] The present invention provides a method for preparing a trace metal-modified perovskite oxide, and the specific steps are as follows: LaMO3-type perovskite oxide precursors were prepared by sol-gel method using lanthanum and non-noble metal salts; A LaMO3 type perovskite oxide precursor is subjected to a two-stage temperature-raising heat treatment to obtain a LaMO3 type perovskite oxide; The LaMO3 type perovskite oxide is subjected to surface sulfidation, and then trace metal modification is performed on the surface after sulfidation to obtain a trace metal modified perovskite oxide.

[0009] Further, in the step of preparing a LaMO3 type perovskite oxide precursor by a sol-gel method using lanthanum and a non-noble metal salt, specifically: Dissolving lanthanum and non-noble metal salts in a solvent at a molar ratio of 1:1 to obtain a mixed solution, wherein the total concentration of metal ions in the mixed solution is 0.1 mol / L to 5 mol / L; An organic complexing agent is added to the mixed solution, and the mixture is heated under acidic conditions for reaction, and then evaporated to dryness and crushed to obtain a LaMO3 type perovskite oxide precursor.

[0010] Further, in the step of subjecting the LaMO3 type perovskite oxide precursor to a two-stage temperature-raising heat treatment to obtain the LaMO3 type perovskite oxide, specifically: A first stage of temperature heating treatment, specifically: placing the LaMO3 type perovskite oxide precursor in an air or oxygen atmosphere, heating it to 400-500°C at a heating rate of 5°C / min-20°C / min, maintaining it for 120-240 minutes, cooling it to room temperature at a rate of 8°C / min-20°C / min, and crushing it to obtain reactant 1; The two-stage temperature-raising heat treatment is specifically as follows: the reactant 1 is placed in an air or oxygen atmosphere, heated to 600-800°C at a heating rate of 5°C / min-20°C / min, maintained for 300-800 minutes, and then cooled to room temperature at a rate of 5°C / min-25°C / min to obtain LaMO3-type perovskite oxide.

[0011] Further, in the step of performing surface sulfidation on the LaMO3 type perovskite oxide, and performing trace metal modification on the surface after sulfidation to obtain the trace metal modified perovskite oxide, specifically: In a nitrogen or argon atmosphere, a sulfur-containing substance is deposited on the surface of a LaMO3 type perovskite oxide by vapor deposition. The specific operating conditions of the vapor deposition are: the sulfur-containing substance is placed upstream of the gas, and the LaMO3 type perovskite oxide is placed downstream of the gas, and the temperature is increased to 300°C~400°C at a heating rate of 5°C / min~30°C / min, and after maintaining for 20min~80min, the temperature is reduced to room temperature at a rate of 10°C / min~30°C / min to obtain a surface-sulfurized LaMO3 type perovskite oxide; or Under the condition of introducing 5 sccm to 20 sccm hydrogen sulfide gas, heat treatment is performed to obtain surface-sulfurized LaMO3 type perovskite oxide.

[0012] Further, in the step of performing surface sulfidation on the LaMO3 type perovskite oxide, and performing trace metal modification on the surface after sulfidation to obtain the trace metal modified perovskite oxide, specifically: Ultrasonic dispersion of the surface-sulfurized LaMO3 type perovskite oxide in a 0.001 mol / L to 0.05 mol / L metal salt solution to obtain a mixed solution 1 having a LaMO3 type perovskite oxide concentration of 10 mg / L to 200 mg / L; Under continuous stirring, the mixed solution 1 is reacted at a microwave power of 150 W to 600 W for 2 min to 10 min to obtain a trace metal-modified perovskite oxide.

[0013] The present invention also provides a catalyst, comprising the above-mentioned trace metal-modified perovskite oxide.

[0014] The present invention also provides a catalytic electrode, wherein the catalyst is loaded on an electrode substrate, and the loading amount of the catalyst is 1 mg / cm 2~5mg / cm 2 .

[0015] Compared with the prior art, the present invention has at least the following beneficial effects: The invention proposes a perovskite oxide modified with trace metals. The introduction of the sulfide layer and the trace metal modification layer enhances the structural stability of the perovskite oxide, so that it can maintain stable catalytic performance during long-term use. The catalytic performance of the perovskite oxide is significantly improved by the modification of trace metals, so that it exhibits higher activity and selectivity in electrochemical reactions. This material is not only suitable for electrochemical applications, but may also be expanded to multiple fields such as hydrogen energy, carbon capture and utilization, and catalysis, showing a wide range of application potential.

[0016] The present invention adopts a sol-gel method combined with high-temperature calcination, and combines the steps of sulfurization, adsorption, reduction, etc. to prepare trace metal-modified perovskite oxides. By accurately controlling the reaction conditions and the proportion of raw materials, the precise regulation of the product structure and performance can be achieved. The preparation method has clear steps, is easy to understand and operate, and is suitable for large-scale industrial production.

[0017] The present invention uses a trace metal-modified perovskite oxide as a catalyst. Since the trace metal-modified perovskite oxide is used as an active ingredient, the catalyst exhibits efficient catalytic performance, can significantly improve the reaction rate and selectivity, and the catalyst can maintain a stable structure and performance during use, prolonging the service life and reducing the replacement frequency and cost; the catalyst is suitable for various chemical reaction types, including oxidation, reduction, hydrogenation, dehydrogenation, etc., and has broad application prospects.

[0018] By loading a trace amount of metal-modified perovskite oxide catalyst on the electrode substrate, the catalytic performance of the electrode is significantly improved, enabling it to efficiently carry out electrochemical reactions; the catalytic electrode can maintain stable catalytic performance during use, reducing the replacement and maintenance costs caused by performance degradation. The preparation method of the catalytic electrode is simple and clear, easy to achieve industrial production, and reduces production costs; the catalytic electrode can be widely used in fuel cells, water electrolysis to produce hydrogen, electrochemical sensors and other fields, and has broad market prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Schematic diagram of the process of the present invention; Figure 2 Bulk LCO perovskite oxide obtained without step-by-step treatment (A), LCO nanoparticles obtained with step-by-step treatment (B), and metal-modified LCO nanoparticles (C); Figure 3 XPS spectrum of Example 1; Figure 4 Electrochemical active area comparison diagram; Figure 5 Comparison of performance of water electrolysis to produce hydrogen; Figure 6 CO2 reduction performance comparison chart. DETAILED DESCRIPTION

[0020] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.

[0021] The present invention provides a perovskite oxide modified with trace metals, wherein the perovskite oxide is synthesized by a sol-gel method using metal salts, and the surface of the perovskite oxide is modified with trace metals by sulfidation, adsorption, reduction, etc., thereby significantly improving the catalytic performance of the perovskite oxide. The main process is as follows Figure 1 The main links are as follows: 1. Preparation of Perovskite Oxide Precursors First, lanthanum (La) and 1-2 non-precious metal salts [nickel (Ni), iron (Fe), cobalt (Co), manganese (Mn), etc.] are selected and added to a mixed solution of ethylene glycol, ethanol and water at a molar ratio of 1:1 (metal lanthanum: non-precious metal), and the total concentration of metal ions is 0.1-5 mol / L. After ultrasonic dissolution, continuous stirring (mechanical or magnetic) is performed at room temperature to obtain a clear solution, and then an organic complexing agent (the molar ratio of the organic complexing agent to lanthanum is 2-4) is added. After complete dissolution, the pH of the solution is adjusted to between 3 and 5. Then, continuous stirring is performed at 60°C-90°C (preferably 75°C) until the solution is evaporated and expanded into a fluffy solid. With the addition of ethanol (ethanol: solid mass ratio = 1:10), the solid is ground into powder (≥60 mesh) to obtain a perovskite oxide precursor.

[0022] Preferably, the metal salts include: lanthanum acetate, lanthanum nitrate; nickel nitrate, nickel chloride, nickel acetate; ferric nitrate, ferric chloride, ferric acetate; cobalt nitrate, cobalt chloride, cobalt acetate; manganese acetate, manganese nitrate, manganese chloride; and hydrates of the above substances.

[0023] Preferably, in the mixed solution, the proportion of ethylene glycol is no more than 15% (volume), and the volume ratio of ethanol to water is between 0 and 1.

[0024] 2. Perovskite oxide thermal forming The solid powder is heat treated in an air or oxygen atmosphere. First, the temperature is raised to 400-500°C (preferably 450°C) at a heating rate of 5-20°C / min (preferably 10°C / min), maintained for 120-240 minutes, and then cooled to room temperature at a rate of 8-20°C / min (preferably 10°C / min); The solid was then ground into powder (≥60 mesh) with the addition of ethanol (ethanol: solid mass ratio = 1:10), followed by a second heating.

[0025] In an air or oxygen atmosphere, the temperature is increased to 600-800°C (preferably 750°C) at a heating rate of 5-20°C / min (preferably 8°C / min), maintained for 300-800min (preferably 480min), and then cooled to room temperature at a rate of 5-25°C / min (preferably 10°C / min) to obtain LaMO3-type perovskite oxide (M = one or two of Ni, Fe, Co, and Mn).

[0026] The use of graded heat treatment combined with grinding in this step helps to avoid material agglomeration and makes it easier to obtain nano-particle-sized perovskite oxides; higher temperatures and longer times often produce more stable products.

[0027] 3. Surface vulcanization With the aid of ethanol (ethanol: solid mass ratio = 1:10), the perovskite oxide is ground into powder (≥120 mesh), and the surface of the perovskite oxide is sulfurized by vapor deposition. That is, in a nitrogen or argon atmosphere, a sulfur-containing substance (sulfur powder, sodium thiosulfate, thioacetamide, etc.) is placed upstream of the gas, and the perovskite oxide powder is placed downstream of the gas, and the temperature is raised to 300~400℃ (preferably 350℃) at a heating rate of 5~30℃ / min (preferably 20℃), maintained for 20~80min (preferably 40min), and then cooled to room temperature at a rate of 10~30℃ / min (preferably 20℃ / min) to complete the surface sulfurization.

[0028] Alternatively, heat treatment is performed under the condition of introducing hydrogen sulfide gas (5-20 sccm, preferably 10 sccm) to complete the sulfidation.

[0029] 4. Surface modification and curing The sulfided perovskite solid oxide is washed with ethanol or acetone for 3 times, collected by filtration or centrifugation, dried in a vacuum oven (60-85°C, preferably 80°C; 5-12h, preferably 8h), and ultrasonically dispersed in a 0.001-0.05mol / L metal salt ethanol / water mixed solution, with a perovskite oxide concentration of 10-200mg / L. Under continuous stirring, it is placed in a microwave reactor with a microwave power of 150 to 600W and a reaction time of 2-10min to complete the metal micro-modification on the surface of the perovskite oxide (≤2 wt %), to obtain trace metal modified perovskite oxides, such as Figure 2 As shown in C.

[0030] Preferred metal salts include silver nitrate, chloroauric acid, copper nitrate, copper acetate, copper chloride, copper bromide, chloroplatinic acid, sodium chloroplatinate, etc. Preferably, the volume ratio of ethanol / water mixed solution is between 0.1 and 3; 5. Catalytic Electrode Preparation Weigh a certain amount of solid powder and disperse it in an alcohol-water solution with a concentration of 10 mg / mL~25 mg / mL (preferably 15). After ultrasonic dispersion, add the ionomer solution. After ultrasonic dispersion, spray it on a substrate (nickel felt, nickel mesh, nickel foam, stainless steel felt, titanium felt, carbon paper, etc.) to obtain a catalytic electrode with a loading of 1 mg / cm 2 ~5mg / cm 2 ,stand-by.

[0031] Preferably, alcohol-water solution: alcohol (methanol / ethanol / isopropanol / propanol), alcohol-water mass ratio is 1-3; Preferably, the ratio of ionomer to catalyst: mass ratio, 0.1 to 0.3, preferably 0.2; Example 1 Weigh 86.6 mg of lanthanum nitrate hexahydrate (molecular weight: 433.01) and 58.2 mg of cobalt nitrate hexahydrate (molecular weight: 291.03) respectively, and add them to 100 mL of water / ethanol / ethylene glycol mixed solution (volume ratio 6:2:1) while stirring. Dissolve by ultrasonic, add 96.1 mg of citric acid (molecular weight: 192.12) while stirring with a magnetic stirrer (300 rpm), and then adjust the pH value of the system to 3.5 with 1 mol / L nitric acid solution. Then continue stirring at 75 ° C until the solution evaporates and expands into a fluffy solid. Grind the solid into 80 mesh powder with the aid of ethanol (ethanol: solid mass ratio = 1:10).

[0032] The solid was transferred to a muffle furnace, heated to 450°C at a heating rate of 10°C / min in an air atmosphere, maintained at 450°C for 180 min, cooled to room temperature at a rate of 10°C / min, and then ground to 80-mesh powder with the aid of ethanol (ethanol: solid mass ratio = 1:10); The mixture was transferred to a muffle furnace, and heated to 750° C. at a rate of 8° C. / min in an air atmosphere, maintained at 480 min (preferably 480 min), and then cooled to room temperature at a rate of 10° C. / min to obtain LaCoO 3 (LCO) perovskite oxide.

[0033] With the assistance of ethanol (ethanol: solid mass ratio = 1:10), LCO was ground into a powder with a particle size of 120 mesh, 50 mg was weighed and placed in the downstream of the temperature zone of the tube furnace, 100 mg of sulfur powder was placed upstream, and the temperature was raised to 350°C at a rate of 20°C / min (preferably 20°C) in a nitrogen atmosphere (10sccm), maintained for 40 minutes, and cooled to room temperature at a rate of 20°C / min to complete the surface sulfurization. The sulfurized LCO was washed with ethanol three times, the solid powder was collected by filtration, and dried in a vacuum oven (80°C, 8h) to obtain sulfurized LCO solid powder.

[0034] 10 mg of LCO solid was weighed and ultrasonically dispersed in 100 mL of a 0.01 mol / L silver nitrate ethanol / water mixed solution (ethanol: water = 1:1). The mixture was placed in a microwave reactor with continuous stirring at a microwave power of 210 W and a reaction time of 5 min to complete the micro-modification of silver on the surface of the perovskite oxide. Figure 2 The bulk LCO perovskite oxide of A is prepared by a non-step-wise processing method, and the obtained bulk material is a micron-scale lanthanum cobalt perovskite oxide; Figure 2 The LCO particles of B were prepared by a step-by-step treatment method, and the obtained particles were lanthanum cobalt perovskite oxide nanoparticles (particle size about 200 nm). Figure 2 C is the metal-modified LCO nanoparticle of Example 1, whose surface layer is a mixed layer of a small amount of silver and lanthanum cobalt perovskite oxide, which is in a flower shape, and the substrate is lanthanum cobalt perovskite oxide nanocrystals. The particle size of the obtained silver-modified lanthanum cobalt perovskite oxide nanoparticles is about 200 nm.

[0035] Figure 3 This is the XPS spectrum of the silver-modified lanthanum cobalt perovskite oxide nanoparticles prepared in Example 1. The presence of Co and Ag elements and their respective binding energy values ​​in the figure indicate that silver has been successfully modified onto the surface of the lanthanum cobalt perovskite oxide nanoparticles.

[0036] like Figure 4 As shown, the electrochemical surface activity area (ECSA) of the test bulk LCO perovskite oxide, LCO particles and silver-modified lanthanum cobalt perovskite oxide nanoparticles of Example 1 was evaluated by the capacitance method. The slope is proportional to the electrochemical surface area of ​​the material. It can be seen that the ECSA of Example 1 is significantly larger, which means that it has more active sites and better catalytic activity.

[0037] Unmodified LCO and trace silver-modified LCO catalysts were coated on Ni felt (loading 3 mg / cm 2 ), select 40 wt% of Pt / C as the cathode catalyst was sprayed on the surface of the FAA3 (Fuma-tech) anion exchange membrane with a loading of 1.25 mg / cm 2 , which was assembled with the anode electrode into a membrane electrode. 1 M KOH was used as the electrolyte, and water electrolysis hydrogen production tests were carried out in an electrolytic cell. The FAA3 anion exchange membrane electrode sprayed with both Pt / C and IrO2 was used as a comparative sample and tested under the same conditions. The results are as Figure 5 . Under the condition of 1 A / cm 2 , the overpotential order of the three membrane electrodes was slightly metal-modified LCO < IrO2 < LCO, proving that the water electrolysis performance of slightly metal-modified LCO was significantly improved and had good application prospects.

[0038] Example 2 Weighed 86.6 mg of lanthanum nitrate hexahydrate (molecular weight: 433.01) and 58.2 mg of nickel nitrate hexahydrate (molecular weight: 290.79) respectively, and added them to 100 mL of a water / ethanol / ethylene glycol mixed solution (volume ratio 3:1:0.4) under stirring. After ultrasonic dissolution, 110.3 mg of citric acid (molecular weight: 192.12) was added under magnetic stirring (300 rpm), and then the pH value of the system was adjusted to 3.5 using 1 mol / L nitric acid solution. Subsequently, continuous stirring was carried out at 75 °C until the solution evaporated and swelled into a fluffy solid. With the assistance of ethanol (ethanol: solid mass ratio = 1:10), the solid was ground into a powder with a mesh size of 80.

[0039] Transferred to a muffle furnace, heated to 450 °C at a heating rate of 10 °C / min in an air atmosphere, held for 180 min, cooled to room temperature at a rate of 10 °C / min, and then ground into a powder with a mesh size of 80 with the assistance of ethanol (ethanol: solid mass ratio = 1:10); Transferred to a muffle furnace, heated to 750 °C at a rate of 8 °C / min in an air atmosphere, held for 480 min, and then cooled to room temperature at a rate of 10 °C / min to obtain LaNiO3 (LNO) perovskite oxide.

[0040] With the assistance of ethanol (ethanol: solid mass ratio = 1:10), LNO was ground into a powder with a particle size of 120 mesh. 50 mg was weighed and placed downstream of the temperature zone of the tubular furnace. Under a hydrogen sulfide atmosphere (10 sccm), it was heated to 350 °C at a heating rate of 20 °C / min, held for 30 min, and cooled to room temperature at a rate of 20 °C / min to complete surface sulfidation. The sulfided LNO was washed 3 times with ethanol, and the solid powder was collected by suction filtration and dried in a vacuum oven (80 °C, 8 h) to obtain surface-sulfided LNO.

[0041] 10 mg of LNO solid was weighed and ultrasonically dispersed in 100 mL of 0.05 mol / L copper acetate alcohol / water mixed solution (ethanol: water = 1:1). Under continuous stirring, it was placed in a microwave reactor with a microwave power of 250 W and a reaction time of 5 min to complete the micro-modification of copper on the surface of perovskite oxide.

[0042] Unmodified LNO and trace copper-modified LNO catalysts were coated on carbon paper (loading 3 mg / cm 2 ) as the working electrode, nickel foam as the counter electrode, Hg / HgO as the reference electrode, and 1M KOH as the electrolyte were used to test the CO2 reduction reaction in the flow cell. The results are shown in Figure 6 The copper-modified LNO exhibited high CO selectivity in the test range, with a maximum Faraday efficiency of 90.2%, while the main product of the unmodified LNO was hydrogen (H2), and the CO product selectivity was less than 6%, demonstrating the feasibility of the metal trace modification scheme.

[0043] Example 3 Weigh 66.8 mg of lanthanum acetate hydrate (molecular weight: 334.05) and 38.2 mg of ferric acetate (molecular weight: 190.94) respectively, and add them to 100 mL of water / ethanol / ethylene glycol mixed solution (volume ratio 3:1:0.3) while stirring. Dissolve by ultrasonication, add 110.3 mg of citric acid (molecular weight: 192.12) while stirring with a magnetic stirrer (300 rpm), and then adjust the pH value of the system to 4 with 1 mol / L acetic acid solution. Then continue stirring at 75 ° C until the solution evaporates and expands into a fluffy solid. Grind the solid into 80 mesh powder with the aid of ethanol (ethanol: solid mass ratio = 1:10).

[0044] The solid was transferred to a muffle furnace, heated to 450°C at a heating rate of 10°C / min in an air atmosphere, maintained at 450°C for 180 min, cooled to room temperature at a rate of 10°C / min, and then ground to 80-mesh powder with the aid of ethanol (ethanol: solid mass ratio = 1:10); The sample was transferred to a muffle furnace, and the temperature was increased to 750°C at a rate of 8°C / min in an air atmosphere, maintained at that temperature for 360 min, and then cooled to room temperature at a rate of 10°C / min to obtain LaFeO3 (LFO) perovskite oxide.

[0045] With the aid of ethanol (ethanol: solid mass ratio = 1:10), LFO was ground into a powder with a particle size of 120 mesh, 50 mg was weighed and placed in the downstream of the temperature zone of the tube furnace, and heated to 350°C at a rate of 20°C / min in a hydrogen sulfide atmosphere (10 sccm), maintained for 30 minutes, and cooled to room temperature at a rate of 20°C / min to complete the surface sulfurization. The sulfurized LFO was washed with ethanol three times, the solid powder was collected by filtration, and dried in a vacuum oven (80°C, 8h) to obtain the surface-sulfurized LFO.

[0046] Weigh 10 mg of LFO solid and ultrasonically disperse it in 100 mL of 0.01 mol / L copper nitrate alcohol / water mixed solution (ethanol: water = 1:1). Place it in a microwave reactor with continuous stirring at a microwave power of 240 W and a reaction time of 4 min to complete the micro-modification of copper on the surface of perovskite oxide.

[0047] Unmodified LFO and trace copper-modified LFO catalysts were coated on carbon paper (loading 3 mg / cm 2 ) as the working electrode, nickel foam as the counter electrode, Hg / HgO as the reference electrode, and 1M KOH as the electrolyte to test the CO2 reduction reaction in a flow cell. The copper-modified LFO showed high CO selectivity in the test range, with a Faradaic efficiency of up to 88.3%, while the main product of the unmodified LFO was hydrogen (H2), and the CO product selectivity was less than 3%.

[0048] Example 4 Weigh 66.8 mg of lanthanum acetate hydrate (molecular weight: 334.05) and 38.2 mg of manganese (III) acetate hydrate (molecular weight: 268.1) respectively, and add them to 100 mL of water / ethanol / ethylene glycol mixed solution (volume ratio 3:1:0.3) under stirring. Dissolve by ultrasonication, add 110.3 mg of citric acid (molecular weight: 192.12) under magnetic stirring (300 rpm), and then adjust the pH value of the system to 4 with 1 mol / L acetic acid solution. Then continue stirring at 75 ° C until the solution evaporates and expands into a fluffy solid. Grind the solid into 80 mesh powder with the aid of ethanol (ethanol: solid mass ratio = 1:10).

[0049] The mixture was transferred to a muffle furnace and heated to 450°C at a heating rate of 10°C / min in an air atmosphere, maintained at that temperature for 200 min, cooled to room temperature at a rate of 10°C / min, and then ground to 80-mesh powder with the aid of ethanol (ethanol: solid mass ratio = 1:10); The sample was transferred to a muffle furnace, and the temperature was increased to 750°C at a rate of 8°C / min in an air atmosphere, maintained at that temperature for 360 min, and then cooled to room temperature at a rate of 10°C / min to obtain LaMnO3 (LMO) perovskite oxide.

[0050] With the assistance of ethanol (ethanol: solid mass ratio = 1:10), LMO was ground into a powder with a particle size of 120 mesh, 50 mg was weighed and placed in the downstream of the temperature zone of the tube furnace, and heated to 350°C at a rate of 20°C / min in a hydrogen sulfide atmosphere (10sccm), maintained for 30min, and cooled to room temperature at a rate of 20°C / min to complete the surface sulfurization. The sulfurized LMO was washed with ethanol three times, the solid powder was collected by filtration, and dried in a vacuum oven (80°C, 8h) to obtain the surface-sulfurized LMO.

[0051] 10 mg of LMO solid was weighed and ultrasonically dispersed in 100 mL of a 0.02 mol / L chloroplatinic acid alcohol / water mixed solution (ethanol: water = 1:1). Under continuous stirring, it was placed in a microwave reactor with a microwave power of 300 W and a reaction time of 3 min to complete the micro-modification of platinum on the surface of the perovskite oxide.

[0052] Unmodified LMO and trace amount of Pt modified LMO catalysts were coated on the rotating disk electrode (loading amount 1 mg / cm 2 ) as the working electrode, platinum wire as the counter electrode, Ag / AgCl as the reference electrode, 1M HClO4 as the electrolyte, and ORR test was performed under continuous oxygen flow. The half-wave potentials of unmodified LMO and platinum-modified LMO are 0.84V and 0.89V, respectively, and the effect of trace platinum modification is significant.

[0053] Example 5 The difference from Example 1 is that the precursor uses 49.8 mg of cobalt acetate tetrahydrate (molecular weight: 249.08) instead of 58.2 mg of cobalt nitrate hexahydrate (molecular weight: 291.03).

[0054] Example 6 The difference from Example 1 is that the precursor uses 47.6 mg of cobalt chloride hexahydrate (molecular weight: 237.93) instead of 58.2 mg of cobalt nitrate hexahydrate (molecular weight: 291.03).

[0055] Example 7 The difference from Example 2 is that the precursor uses 47.5 mg of nickel chloride hexahydrate (molecular weight: 237.69) instead of 58.2 mg of nickel nitrate hexahydrate (molecular weight: 290.79).

[0056] Example 8 The difference from Example 2 is that the precursor uses 49.8 mg of nickel acetate tetrahydrate (molecular weight: 248.84) instead of 58.2 mg of nickel nitrate hexahydrate (molecular weight: 290.79).

[0057] Example 9 The difference from Example 3 is that the precursor uses 80.8 mg of iron nitrate nonahydrate (molecular weight: 404) instead of 38.2 mg of iron acetate (molecular weight: 190.94).

[0058] Example 10 The difference from Example 3 is that 30.0 mg of ferric chloride tetrahydrate (molecular weight: 144.76) is used as the precursor to replace 38.2 mg of ferric acetate (molecular weight: 290.79).

[0059] Embodiment 11 The difference from Example 4 is that 50.2 mg of manganese nitrate tetrahydrate (molecular weight: 251.01) is used as the precursor to replace 38.2 mg of manganese acetate hydrate (molecular weight: 268.1).

[0060] Example 12 The difference from Example 4 is that 25.2 mg of manganese chloride (molecular weight: 125.84) is used as the precursor to replace 38.2 mg of manganese acetate hydrate (molecular weight: 268.1).

[0061] Embodiment 13 The difference from Example 1 is that gold is used instead of silver for surface modification; 10 mg of LCO solid was weighed and ultrasonically dispersed in 100 mL of a 0.02 mol / L chloroauric acid ethanol / water mixed solution (ethanol: water = 1:1). The mixture was placed in a microwave reactor with continuous stirring at a microwave power of 210 W and a reaction time of 5 min to complete the micro-modification of gold on the surface of the perovskite oxide.

[0062] Embodiment 14 The difference from Example 1 is the stirring temperature of the solution gelation; Then, the mixture was stirred continuously at 60°C until the solution evaporated to dryness and expanded into a fluffy solid. The solid was ground into 80 mesh powder with the aid of ethanol (ethanol: solid mass ratio = 1:10).

[0063] Embodiment 15 The difference from Example 1 is the stirring temperature of the solution gelation; Then, the mixture was stirred continuously at 90°C until the solution was evaporated to dryness and expanded into a fluffy solid. The solid was ground into 80 mesh powder with the aid of ethanol (ethanol: solid mass ratio = 1:10).

[0064] Example 16 The difference from Example 1 is the perovskite oxide hot forming temperature; The sample was transferred to a muffle furnace, and the temperature was increased to 600°C at a rate of 8°C / min in an air atmosphere, maintained for 480 min, and then cooled to room temperature at a rate of 10°C / min to obtain LaCoO3 (LCO) perovskite oxide.

[0065] Embodiment 17 The difference from Example 1 is the perovskite oxide hot forming temperature; The mixture was transferred to a muffle furnace, and heated to 800° C. at a rate of 8° C. / min in an air atmosphere, maintained for 480 min (preferably 480 min), and then cooled to room temperature at a rate of 10° C. / min to obtain LaCoO 3 (LCO) perovskite oxide.

[0066] Embodiment 18 The difference from Example 1 is the microwave treatment power; 10 mg of LCO solid was weighed and ultrasonically dispersed in 100 mL of a 0.01 mol / L silver nitrate ethanol / water mixed solution (ethanol: water = 1:1). Under continuous stirring, it was placed in a microwave reactor with a microwave power of 600 W and a reaction time of 5 min to complete the micro-modification of silver on the surface of the perovskite oxide.

[0067] Embodiment 19 The difference from Example 1 is the microwave treatment power; 10 mg of LCO solid was weighed and ultrasonically dispersed in 100 mL of a 0.01 mol / L silver nitrate ethanol / water mixed solution (ethanol: water = 1:1). Under continuous stirring, it was placed in a microwave reactor with a microwave power of 150 W and a reaction time of 5 min to complete the micro-modification of silver on the surface of the perovskite oxide.

[0068] The electrochemical performance indicators of the trace metal modified perovskite oxides prepared in Examples 1 to 19 were tested, and the specific data are shown in the following table:

[0069] By comparing Example 1 with Examples 5 and 6, Example 2 with Examples 7 and 8, Example 3 with Examples 9 and 10, and Example 4 with Examples 11 and 12, it can be seen that replacing the metal salt precursor has no significant effect on the catalytic performance of the final product of the method, which proves the universality of the method proposed in the present invention; By comparing Example 1 with Example 13, it can be seen that the replacement of the metal precursor has a slight effect on the catalytic performance of the final product, but both are significantly better than the unmodified metal perovskite oxide, proving that the trace metal modification described in the present invention has high feasibility and advantages; By comparing Example 1 with Examples 14 and 15, it can be seen that the method of the present invention achieves the beneficial effect of effective polymerization of perovskite oxide by selecting and optimizing the precursor expansion molding temperature, and significantly improves the catalytic performance of the obtained product, which proves the feasibility and advancement of the method of the present invention; By comparing Example 1 with Examples 16 and 17, it can be seen that the method of the present invention effectively controls the particle size and purity of the perovskite oxide by selecting and optimizing the sintering temperature range of the perovskite oxide, and significantly improves the catalytic performance of the obtained product, which proves the feasibility and advancement of the method of the present invention; By comparing Example 1 with Examples 18 and 19, it can be seen that the method of the present invention achieves the beneficial effect of uniform distribution of metal ions by selecting and optimizing the microwave power range of metal-modified perovskite oxide, and significantly improves the catalytic performance of the final product, which proves the feasibility and advancement of the method of the present invention; The present invention uses metal salts as main precursors, adopts a sol-gel method and high-temperature calcination to prepare perovskite oxides, forms perovskite oxides modified with trace metal surfaces by sulfidation, adsorption, reduction and the like, and uses the perovskite oxides modified with trace metal surfaces as catalysts, mainly for electrochemical applications, involving hydrogen energy, carbon capture and utilization, catalysis and other fields, and has good application prospects.

Claims

1. A trace metal-modified perovskite oxide, characterized in that: It includes a LaMO3 type perovskite oxide substrate, a sulfide layer and a trace metal modification layer. The sulfide layer and the trace metal modification layer are sequentially arranged on the surface of the LaMO3 type perovskite oxide substrate, wherein M is a non-precious metal.

2. The trace metal-modified perovskite oxide according to claim 1, characterized in that: In LaMO3-type perovskite oxides, the molar ratio of La to M is 1:

1.

3. The trace metal-modified perovskite oxide according to claim 1, characterized in that: In the LaMO3 type perovskite oxide substrate, M is one or two of nickel, iron, cobalt and manganese; the metal used in the trace metal modification layer is silver, gold, copper or platinum.

4. The method for preparing a trace metal-modified perovskite oxide according to any one of claims 1 to 3, characterized in that: The specific steps are as follows: LaMO3-type perovskite oxide precursors were prepared by sol-gel method using lanthanum and non-noble metal salts; A LaMO3 type perovskite oxide precursor is subjected to a two-stage temperature-raising heat treatment to obtain a LaMO3 type perovskite oxide; The LaMO3 type perovskite oxide is subjected to surface sulfidation, and then trace metal modification is performed on the surface after sulfidation to obtain a trace metal modified perovskite oxide.

5. The method for preparing a trace metal-modified perovskite oxide according to claim 4, characterized in that: In the step of preparing a LaMO3 type perovskite oxide precursor by a sol-gel method using lanthanum and a non-noble metal salt, specifically: Dissolving lanthanum and non-noble metal salts in a solvent at a molar ratio of 1:1 to obtain a mixed solution, wherein the total concentration of metal ions in the mixed solution is 0.1 mol / L to 5 mol / L; An organic complexing agent is added to the mixed solution, and the mixture is heated under acidic conditions for reaction, and then evaporated to dryness and crushed to obtain a LaMO3 type perovskite oxide precursor.

6. The method for preparing a trace metal-modified perovskite oxide according to claim 4, characterized in that: The step of subjecting the LaMO3 type perovskite oxide precursor to a two-stage temperature-raising heat treatment to obtain the LaMO3 type perovskite oxide comprises: A first stage of temperature heating treatment, specifically: placing the LaMO3 type perovskite oxide precursor in an air or oxygen atmosphere, heating it to 400-500°C at a heating rate of 5°C / min-20°C / min, maintaining it for 120-240 minutes, cooling it to room temperature at a rate of 8°C / min-20°C / min, and crushing it to obtain reactant 1; The two-stage temperature-raising heat treatment is specifically as follows: the reactant 1 is placed in an air or oxygen atmosphere, heated to 600-800°C at a heating rate of 5°C / min-20°C / min, maintained for 300-800 minutes, and then cooled to room temperature at a rate of 5°C / min-25°C / min to obtain LaMO3-type perovskite oxide.

7. The method for preparing a trace metal-modified perovskite oxide according to claim 4, characterized in that: In the step of performing surface sulfidation on the LaMO3 type perovskite oxide, and performing trace metal modification on the surface after sulfidation to obtain the trace metal modified perovskite oxide, specifically: In a nitrogen or argon atmosphere, a sulfur-containing substance is deposited on the surface of a LaMO3 type perovskite oxide by vapor deposition. The specific operating conditions of the vapor deposition are: the sulfur-containing substance is placed upstream of the gas, and the LaMO3 type perovskite oxide is placed downstream of the gas, and the temperature is increased to 300°C~400°C at a heating rate of 5°C / min~30°C / min, and after maintaining for 20min~80min, the temperature is reduced to room temperature at a rate of 10°C / min~30°C / min to obtain a surface-sulfurized LaMO3 type perovskite oxide; or Under the condition of introducing 5 sccm to 20 sccm hydrogen sulfide gas, heat treatment is performed to obtain surface-sulfurized LaMO3 type perovskite oxide.

8. The method for preparing a trace metal-modified perovskite oxide according to claim 4, characterized in that: In the step of performing surface sulfidation on the LaMO3 type perovskite oxide, and performing trace metal modification on the surface after sulfidation to obtain the trace metal modified perovskite oxide, specifically: Ultrasonic dispersion of the surface-sulfurized LaMO3 type perovskite oxide in a 0.001 mol / L to 0.05 mol / L metal salt solution to obtain a mixed solution 1 having a LaMO3 type perovskite oxide concentration of 10 mg / L to 200 mg / L; Under continuous stirring, the mixed solution 1 is reacted at a microwave power of 150 W to 600 W for 2 min to 10 min to obtain a trace metal-modified perovskite oxide.

9. A catalyst, characterized in that It comprises a trace metal modified perovskite oxide as claimed in claim 1.

10. A catalytic electrode, characterized in that: The catalyst according to claim 9 is loaded on the electrode substrate, and the loading amount of the catalyst is 1 mg / cm 2 ~5mg / cm 2 .

Citation Information

Patent Citations

  • Perovskite oxide prepared by microwave method for oxygen reduction catalytic reaction

    CN110280237A